A rapid method of hand crossing cowpeas - Rachie, K.O.; Rawal, K.M.; Franckowiak, J.D. (1975)
A cut is made about two-thirds of the width of the unopened, but mature, flower bud, starting in the centre of the upper, straight edge. The upper portion of the folded petals is grasped by the thumb and index finger, lifted outwards and torn free, exposing the style, stigma and anthers, the latter being then cut away with scissors. It is estimated that the method takes 15-25 s per flower. If emasculated in the evening a flower may be pollinated the following morning